Wasit University management of the educational process in accordance with the requirements of sustainable development in light of the Corona pandemic (COVID-19) - Saad Naeem Radhawi (Journal of Sustainability Perspectives, 2022)
The current working paper aimed to reveal the efforts of Wasit University in its management of the educational process in accordance with the requirements of sustainable development in light of the Corona pandemic ((COVID-19), where the university administration invested during the state of emergency all its energies and capabilities and worked to facilitate the tasks, which achieved the superiority of the university in experiencing the transformation experience. To e-learning during the pandemic period the university worked gradually and comprehensively within the emergency plan that came into existence in cooperation between the Board of Directors, the Deans Council and emergency committees and was implemented in cooperation with various authorities. The university adopts a fixed e-learning methodology that is characterized by flexibility, where the teacher records the lecture in video form, whether using PowerPoint with audio recording or screen recording of lectures every week and holding at least one interactive meeting at the same time as the lecture on the academic schedule so that students can watch the lectures at the appropriate times For them or the teacher holds all his lectures interactively directly with the students, provided that all lectures are Interactive at the time of the lecture according to the study schedule, and ways were provided to add solutions to raise the level of security for the content available on Zoom and One drive. A guide was provided for using Zoom not only for interactive meetings, but also for recording off-line lectures and making them available to students on the Moodle platform, and other important guides. The team viewer program was also used to gain access to the computers of teachers who find it difficult to deal with issues related to e-learning and explain it step by step directly, and this method was very effective. The university is now working on developing a specific mechanism to prepare for final exams using e-learning, taking into account the process of remote monitoring and answering students’ inquiries during exams while maintaining the highest levels of academic standards and enhancing quality in education, thus making Wasit University the pioneer in adopting the electronic exam method. It was also revealed in the working paper about the effectiveness of e-learning in light of the spread of the Corona virus from the point of view of the faculty members at Wasit University, and the researcher conducted a survey and to achieve the objectives of the study, the descriptive analytical approach was relied on, and the study sample consisted of (300) faculty members. At the University of Wasit who taught during the period of the spread of the Corona virus through the e-learning system, the necessary data were collected using a questionnaire whose reliability coefficient reached (0.804) and was applied to the study sample. The results of the study revealed that the study sample’s evaluation of the effectiveness of e-learning in light of the spread of the Corona virus from their point of view was average, and their evaluation of the field of e-learning continuity and the field of interaction of faculty members with e-learning, and the field of students’ interaction in the use of e-learning was average, and the researcher recommended holding training courses In the field of e-learning for both teachers and students, and help in benefiting from the e-learning system in higher education institutions in the future.Keyword: Wasit University, management , Educational, Process Corona pandemic (COVID-19)